ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TERWUJUDNYA PEMBAYARAN ZAKAT SEBAGAI PENGURANG PAJAK PENGHASILAN (STUDI DI MASYARAKAT KECAMATAN PAMIJAHAN DAN KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR) - Citra Praditya Rahayu; Rully Trihantana; Ermi Suryani (SAHID BUSINESS JOURNAL, 2022)
The purpose of this study is to identify and analyze the factors that influence the realization of zakat payments as a deduction from income tax. This research was conducted on taxpayers in Pamijahan District and Cibungbulang District, Bogor Regency, by taking a random sample, using a questionnaire as a data collection tool. This study found that there were six dominant factors that influenced the realization of zakat payments as a deduction from income tax, especially for the people of Pamijahan District and Cibungbulang District, Bogor Regency. The six factors are the Organizational Factor with a contribution of 33.611%, the Appreciation Factor with a contribution of 11.684%, the Faith Factor with a contribution of 7.586%, the Satisfaction Factor with a contribution of 6.261%, the Altruism Factor with a contribution of 6.078% and the Concern Factor with a contribution of 5.556. The total of the six percentage of variance or the contribution of each factor has a value of 70.776%, which means that these factors as a whole can answer the factors that influence the realization of zakat payments as a deduction for income tax, especially the people of Pamijahan District and Cibungbulang District, Bogor Regency. And the remaining 29.224% is considered to have no effect on the realization of zakat payments as a deduction from income tax, especially for the people of Pamijahan District and Cibungbulang District, Bogor Regency